Interdisciplinary implementation of tacrolimus intravenous standard concentration in hematopoietic stem cell transplantation recipients. (July 2018) - Shank, Brandon R; Deaver, Melissa; Baker, Angela; Myers, Alan L; Zhang, Yan-Ping; Anderegg, Brent; Bassett, Roland; Westmoreland, Michael
Purpose: Reduction in waste of intravenous (IV) tacrolimus, an immunosuppressant used to prevent graft-versus-host disease in allogeneic hematopoietic stem cell transplantation recipients, was evaluated after standardizing the concentration. Methods: A single-center, retrospective cohort study at a large academic comprehensive cancer center was performed comparing patient-specific intravenous tacrolimus doses (tacrolimus doses in 50, 100, or 250 mL of normal saline based on manufacturer's recommended concentration) to tacrolimus intravenous standard concentration (tacrolimus 1 mg in 250 mL of normal saline) continuous intravenous infusion titrated to prescribed dose. The cohort study was performed on two hematopoietic stem cell transplantation nursing units consisting of a prepilot phase during which time patient-specific intravenous tacrolimus doses were compounded and administered, followed by the pilot phase during which patients received tacrolimus intravenous standard concentration. The primary endpoint was reduction in tacrolimus intravenous bags wasted. Secondary endpoints were drug cost savings, decreased intravenous infusion line supplies, decrease in time needed to execute dose changes, reduction in infusion pump alerts, and number of patient safety events. Results: Compared to the prepilot phase, there was a 64% reduction in tacrolimus intravenous bags wasted during the pilot phase ( p = 0.029), resulting in a mean monthly total cost savings of 224.31 for pilot units. Intravenous pump line use was reduced by 18% ( p = 0.067), yielding a monthly total cost savings of 84.02 for pilot units. The median time needed to execute dose changes and intravenous pump overrides was significantly reduced ( p < 0.0001, p < 0.0001, respectively). Conclusion: This interdisciplinary quality improvement initiative led to increased efficiency, reduction in waste, and decreased intravenous pump alerts utilizing tacrolimus intravenous standard concentration.